Approximation properties of λ‐Bernstein‐Kantorovich operators with shifted knots. (9th April 2019) - Rahman, Shagufta; Mursaleen, Mohammad; Acu, Ana Maria
Abstract : In the present article, Kantorovich variant of λ ‐Bernstein operators with shifted knots are introduced. The advantage of using shifted knot is that one can do approximation on [0, 1] as well as on its subinterval. In addition, it adds flexibility to operators for approximation. Some basic results for approximation as well as rate of convergence of the introduced operators are established. The r t h order generalization of the operator is also discussed. Further for comparisons, some graphics and error estimation tables are presented using MATLAB.